2020
DOI: 10.1002/ange.202003220
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced‐Symmetry Heterobimetallic [PdPtL4]4+ Cage: Assembly, Guest Binding, and Stimulus‐Induced Switching

Abstract: A strategy is presented that enables the quantitative assembly of a heterobimetallic [PdPtL4]4+ cage. The presence of two different metal ions (PdII and PtII) with differing labilities enables the cage to be opened and closed selectively at one end upon treatment with suitable stimuli. Combining an inert PtII tetrapyridylaldehyde complex with a suitably substituted pyridylamine and PdII ions led to the assembly of the cage. 1H and DOSY NMR spectroscopy and ESI mass spectrometry data were consistent with the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 152 publications
0
6
0
Order By: Relevance
“…It has been shown that interaction of such cages with chemical stimuli, e.g., additional ligands, allows structural rearrangement and guest release. 16 The addition of halide anions to positively charged hosts can trigger the uptake of neutral guest molecules. 17 Guest uptake can also be tuned in redox-responsive systems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that interaction of such cages with chemical stimuli, e.g., additional ligands, allows structural rearrangement and guest release. 16 The addition of halide anions to positively charged hosts can trigger the uptake of neutral guest molecules. 17 Guest uptake can also be tuned in redox-responsive systems.…”
Section: Introductionmentioning
confidence: 99%
“…Further expanding on this work, Crowley and coworkers used the subcomponent self‐assembly approach to form heterometallic platinum(II)‐palladium(II) cages using a platinum(II) pyridylaldehyde complex and pyridylamine building blocks (Figure 3b middle) [49a] . This heterometallic monocavity cage was shown to bind both 2,6‐diaminoanthraquinone and 5‐fluorouracil.…”
Section: Molecular Recognitionmentioning
confidence: 99%
“…These cages have also proven useful across diverse areas, including molecular recognition and sensing, [5] chemical separation, [6] stabilization of otherwise unstable species, [7] and catalytic transformations [8] . The reversible linkages between metal vertices and coordination sites can enable these cages to disassemble and reassemble in response to external stimuli, [9] for instance, temperature, [10] light, [11] redox, [12] and pH [13] …”
Section: Figurementioning
confidence: 99%